2001
DOI: 10.1515/crll.2001.034
|View full text |Cite
|
Sign up to set email alerts
|

Hodge structures on abelian varieties of CM-type

Abstract: We show that any effective Hodge structure of CMtype occurs (without having to take a Tate twist) in the cohomology of some CM abelian variety over C. As a consequence we get a simple proof of the theorem (due to Hazama) that the usual Hodge conjecture for the class of all CM abelian varieties implies the general Hodge conjecture for the same class. 1[22] S. G. Tankeev, Abelian varieties and the general Hodge conjecture, Izv. Ross.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In the introduction we listed 7 cases where the general Hodge conjecture for all A i × E j is known, the results of Corollary 3.3 being Cases (6) and (7). Cases (1), (4), and, (5) can be proved similarly. In Cases (2) and (3), the algebraicity of the Weil cycles is not known for a general fiber of the Weil family, but Schoen [19] obtains the general Hodge conjecture in these cases by directly proving the algebraicity of the Weil cycles in A × E w .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In the introduction we listed 7 cases where the general Hodge conjecture for all A i × E j is known, the results of Corollary 3.3 being Cases (6) and (7). Cases (1), (4), and, (5) can be proved similarly. In Cases (2) and (3), the algebraicity of the Weil cycles is not known for a general fiber of the Weil family, but Schoen [19] obtains the general Hodge conjecture in these cases by directly proving the algebraicity of the Weil cycles in A × E w .…”
Section: Resultsmentioning
confidence: 73%
“…In a series of papers [1][2][3][4][5] we have shown that the general Hodge conjecture for certain abelian varieties A is implied by the usual Hodge conjecture for a class of abelian varieties, and used this to prove the general Hodge conjecture in some cases. In this paper we extend these results to certain abelian varieties of type IV.…”
Section: Introductionmentioning
confidence: 99%
“…Let us start with the case where our abelian varieties have no factor of totally real type. The following theorem is due to Abdulali [1, Examples 2 & 3] : Theorem 3.10 (Abdulali [1], strong GHC for powers of CM abelian surfaces and certain products of CM elliptic curves). Let A be an abelian variety that is isogenous to either Proof.…”
Section: 5mentioning
confidence: 99%
“…Nonetheless, the generalized Hodge conjecture was established by Abdulali [1] for powers of a simple abelian surface of CM type (see Theorem 3.10). Abdulali's proof yields a strong form of the generalized Hodge conjecture (as in Conjecture 1.6) for powers of abelian varieties of dimension ≤ 2 (see Corollary 3.13).…”
Section: Introductionmentioning
confidence: 99%
“…In the second case, if M is a torus and hence D M consists of a single point, we say H is of CM type. By [1], every (effective) Hodge structure of CM type occurs in the cohomology of a CM abelian variety. In the case of an elliptic curve E = C/Λ, the property of being CM means that there is a complex number α which is not an integer such that α(Λ) ⊂ Λ, and hence multiplication by α induces a map E → E. The Mumford-Tate conjecture for abelian varieties of CM type was proven by Pohlmann [56].…”
Section: Remark 26 a Morphism Of Hodge Structuresmentioning
confidence: 99%